CURRENT OPPORTUNITIES FOR COMBINATION TREATMENT OF LOWER URINARY TRACT SYMPTOMS DUE TO BENIGN PROSTATIC HYPERPLASIA IN MEN - G. R. Kasyan; I. V. Konovalov (Исследования и практика в медицине)
Lower urinary tract symptoms (LUTS) associated with benign prostatic hyperplasia (BPH) are widely presented, particularly among elderly men. It was commonly accepted that LUTS are directly or indirectly connected with the prostate. Recent studies have shown that mild andsevere forms of LUTS may have a different etiology, such as, bladder related problems: overactive bladder (OAB)/detrusor overactivity or, conversely, an underactive bladder due to compromised contractions of the detrusor. There are three main groups of LUTS: storage symptoms, voiding symptoms and post-micturition symptoms. Patients with LUTS/BPH who are not sufficiently respond to monotherapy with alpha-blockers should receive additional treatment with M‑anticholinergics in accordance with the European urological guidelines. Current studies show that up to 65% of patients with LUTS/BPH with symptoms of urgency and frequency do not have sufficient reduction of symptoms after 3 months of treatment with alphablocker as monotherapy. Until recently, alpha-blockers and M‑anticholinergic medications were prescribed in combination therapy as a two separate pills. Vesomni is a combination of antimuscarinic drug solifenacin 6 mg with α1‑blocker tamsulosin OCAS 0.4 mg in one tablet. It is developed to relieve storage (urgency and frequency) and voiding symptoms in men with LUTS/BPH. Solifenacin suppresses the overactivity of the detrusor and reduces storage symptoms. Tamsulosin OCAS relaxes smooth muscle of the prostate, prostatic urethra and bladder neck, and eliminates most voiding symptoms and, to a lesser extent, storage symptoms.